Wave propagation and power deposition in blue-core helicon plasma - Chang, L.; Caneses, J. F.; Thakur, S. C. (Frontiers in Physics, 2022)
The wave propagation and power deposition inside and outside the blue-core helicon plasma are computed, together with their transitional behaviours prior to and after the blue-core formation. Computations refer to the experiments on the CSDX (controlled shear decorrelation experiment) (Thakur et al., Plasma Sources Science and Technology 23: 044006, 2014 and Thakur et al., IEEE Transactions on Plasma Science 43: 2754–2759, 2015). It is found that the radial profile of wave electric field peaks off-axis during the blue-core formation, and the location of this peak is very close to that of particle transport barrier observed in experiment; the radial profile of wave magnetic field shows multiple radial modes inside the blue-core column, which is consistent with the experimental observation of coherent high $m$ modes through Bessel function. The axial profiles of wave field indicate that the decay length shortens for increased external field strength, especially when the blue-core mode has been achieved, and this length is relatively longer inside the core than that outside. The wave energy density is overall lower in two orders after blue-core formation than that prior to, and the energy distribution shows a periodic boundary layer near the edge of blue-core column. The dispersion relation inside the blue-core column suggests the presence of two radial modes, while outside the blue-core column it shows no variation, i.e. constant wave number with changed frequency. The power deposition appears to be off-axis in the radial direction, forming a hollow profile, and when the blue-core mode has been formed it shows periodic structure in the axial direction. Analyses based on the step-like function theory and introduced blue-core constant provide consistent results and more physics understanding. These details of wave propagation and power deposition during the blue-core formation are presented for the first time, and helpful for understanding the mechanism of blue-core phenomenon. The equivalence of blue-core plasma column to optical fiber for electromagnetic communication is also explored, and preliminary calculation shows that total reflection can indeed occur if the incident angle is larger than a threshold value. This may inspire a novel application of helicon plasma, ...